Military medicine and morale: Perceptions of inequities in triage impact national security - Tanisha M. FAZAL; Jane L. SUMNER; Jessica KORONA-BAILEY; Tracey Pérez KOEHLMOOS (Journal of Health and Social Sciences, 2024)
Introduction: There is an established relationship between military morale and battlefield effectiveness. Theoretically, better military medicine should increase morale leading to increased effectiveness as such we sought to investigate the relationship between military medicine and military morale. Methods: We conducted a survey experiment of active-duty service members aged 18-62 years. The virtual survey was advertised in a social media campaign using Meta from July 23, 2022, through July 20, 2023. Service members were randomly assigned scenarios regarding a theoretical conflict. One set of scenarios included a triage protocol where mission-essential personnel would be prioritized for medical care even if not the most severely injured. The other set of scenarios did not mention triage. A Total Morale Index score was developed. Linear regression was used to test the relationship between military medicine and morale adjusting for treatment conditions and covariates of age, rank, and service years. Results: The final sample was comprised of 1808 active-duty service members mean age of 25.28 years ± 7.7 standard deviation and 87.5% male. Respondents who received the triage treatment consistently reported lower morale compared to respondents who did not receive the triage treatment controlling for demographic and military-specific factors; this difference was statistically significant at the p=.05 level. Women, married respondents, and those with a longer time in their unit had lower morale scores. Discussion: Respondents who received a randomly assigned prompt indicating that they would be less likely to receive medical care if injured on the battlefield report significantly lower levels of morale compared to respondents who did not receive this prompt. Given that prior research has demonstrated a relationship between military morale and military effectiveness, investments in military medicine can contribute to effectiveness by improving morale.